The Effect of Cupping Therapy on Pain Degree in Athralgia - Kusworini (Arkus, 2021)
Joint inflammation characterized by swelling of the joints, redness, heat, pain and movement disorders. Arthralgia causes the elderly to have difficulty in carrying out activities that are burdening the joints of the body. Wet cupping therapy is a complementary therapy that has a working principle of vacuum, injury and blood-sucking in certain areas so it can cure the disease. This study was to identify the effect of cupping therapy on pain intensity in elderly patients with arthralgia in Malang. It was a quasy experiment research with pretest-posttest with control group approach. The sample in this study was 30 elderly then divided into two groups, i.e. 15 elderly in the wet cupping therapy group and 15 elderly in the warm compress group. It used purposive sampling. The average pain intensity before moist cupping therapy was 7.47, and after wet cupping therapy 5.53. While the moderate pain intensity before warm compress was 7.00 and after warm compress 5.73. Wilcoxon test results moist cupping therapy obtained P-value 0.001 means there are significant differences before and after the wet cupping therapy. While Wilcoxon test results, warm compress got P-value 0.001 means there are substantial differences before and after the warm compress. Mann Whitney test result obtained P-value 0.383 means there is no significant difference of effect between the treatment group and the control group. There is an effect of cupping therapy and warm compress on pain intensity. Elderly can use wet cupping therapy as an alternative treatment to decrease joint pain intensity arthralgia.